Original article HDR brachytherapy of prostate cancer – two years experience in Greater Poland Cancer Centre - Kanikowski, Marek; Skowronek, Janusz; Chicheł, Adam (Journal of Contemporary Brachytherapy, 2009)
Purpose: The aim of this work was to analyze the results and complications of three treatment schemes of patients with initially localized prostate cancer after two years of observation time. Material and methods: Sixty-three patients were enrolled into the study and divided into groups according to radiation schemes (I group – EBRT 50 Gy/BRT 15 Gy, II – EBRT 46 Gy/BRT 2 × 10 Gy, III group – BRT 3 × 15 Gy). Group I, II and III consisted of 46 (73%), 14 (22.2%), 3 (4.8%) patients, respectively. The low-, intermediate- and high risk groups consisted of 23 (36.5%), 18 (28.5%) and 22 (35%) men, respectively. Results and tolerance of the treatment and acute complications in analyzed groups were discussed. Results: Median observation time was 24 months. Complete remission was observed in 43 patients (68.3%) out of the whole group. Locoregional and distal metastases progression were noted in 4 patients (6.4%). Partial remission was observed in low-, intermediate- and high risk group: 7.9%, 9.5% and 9.5% of all men. Nadir of PSA results were estimated as mean value of 0.094 ng/ml, average 0.0-0.63. The mean value for the complete group decreased from 0.98 ng/ml (range 0.0-9.7) in the third months to 0.32 ng/ml after one year (0.0-3.34) of the end of treatment time. Urologic and gastrointenstinal side effects were noted in different rates according to 1 month observation (dysuria – 22.2%, urinary incontinence – 7.9%, frequency – 58.7%, weak stream – 68.3%, rectal bleeding – 15.9%). Conclusions: 1. HDR brachytherapy of prostate cancer can be used as a boost after or before the external beam radiation therapy in different treatment schemes. 2. In selected groups under investigation trials, sole HDR-BRT is a suitable method of treatment. 3. To confirm superiority of analyzed modality treatment a prospective investigation with larger groups of patients would be required.